PATIENTS WITH HIV INFECTION IN A DISTRITAL HOSPITAL - Sá, Joana (1996)
The authors present a retrospective analysis of HIV infected patients treated in an Internai Medicine Ward, from January 1992 to June 1995. The following parameters were analysed: number of admissions per patient, time of permanence in the hospital, opportunistic complications, final outcome, medical counselling at leaving and distribution according to sex, age, ethnic, infectious virus, risk group and staging. From the results one can highlight the following: 61 patients were admitted, with a total of 134 admissions: 20 in 1992, 35 in 1993, 60 in 1994 and 19 during the first semester of 1995. 57% of the patients were drugs addicts and the most frequent opportunistic infection was tuberculosis. Of the 202 opportunistic complications observed, we could reach an accurate diagnosis in 47,6% of the cases. The average time of permanence in the hospital was 15,8 days. Mortality was 10% and 94% of the patients were sent to the outpatient clinic of Infectious Diseases. The authors tried to match the results with the social and economical situation, comparing them with other national casuisty. The authors conclusion is that the HIV infection is more and more an important reason of admission, even in District Hospitals and in Internal Medicine Wards.